The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1002/eji.200737581
|View full text |Cite
|
Sign up to set email alerts
|

Endoglycosidase treatment abrogates IgG arthritogenicity: Importance of IgG glycosylation in arthritis

Abstract: The glycosylation status of IgG has been implicated in the pathology of rheumatoid arthritis. Earlier, we reported the identification of a novel secreted endo-b-Nacetylglucosaminidase (EndoS), secreted by Streptococcus pyogenes that specifically hydrolyzes the b-1,4-di-N-acetylchitobiose core of the asparagine-linked glycan of human IgG. Here, we analyzed the arthritogenicity of EndoS-treated collagen type II (CII)-specific mouse mAb in vivo. Endoglycosidase treatment of the antibodies inhibited the induction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
98
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 64 publications
3
98
0
Order By: Relevance
“…In contrast to PNGaseF, this enzyme does not remove the entire sugar moiety but keeps one N-acetylglucosamine (GlcNAc) of the core sugar structure and its branching fucose residue that is present in the majority of the serum IgG pool. In our previous studies, we were able to show that treatment of mouse and human IgG subclasses with EndoS in vitro results in a severely reduced affinity to cellular Fc␥Rs (7,10). Injection of EndoS-treated autoantibody preparations generated in rabbits resulted in a dramatic reduction of antibody activity in vivo, further supporting the notion that cellular Fc␥Rs are the crucial mediators of antibody activity (9).…”
Section: Igg Antibodies Are Potent Inducers Of Proinflammatory Responmentioning
confidence: 69%
See 3 more Smart Citations
“…In contrast to PNGaseF, this enzyme does not remove the entire sugar moiety but keeps one N-acetylglucosamine (GlcNAc) of the core sugar structure and its branching fucose residue that is present in the majority of the serum IgG pool. In our previous studies, we were able to show that treatment of mouse and human IgG subclasses with EndoS in vitro results in a severely reduced affinity to cellular Fc␥Rs (7,10). Injection of EndoS-treated autoantibody preparations generated in rabbits resulted in a dramatic reduction of antibody activity in vivo, further supporting the notion that cellular Fc␥Rs are the crucial mediators of antibody activity (9).…”
Section: Igg Antibodies Are Potent Inducers Of Proinflammatory Responmentioning
confidence: 69%
“…1A). We and others have shown that EndoS efficiently hydrolyzes the IgG-associated sugar moiety in human and rabbit serum and on purified antibodies (7,9,10). Because the focus of this work was to investigate the effect of EndoS application in mouse in vivo models of induced and established autoimmune disease, we first set out to identify the conditions for optimal IgG glycan hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This hypothesis was further stimulated by our recent finding that pretreatment of arthritogenic autoantibodies with EndoS abrogates the development of disease in a mouse model of collagen-induced arthritis (23). The IgG-specific protease IdeS also has been shown to be efficient in a similar model system (24) and in the mouse model of ITP used in this study (25).…”
mentioning
confidence: 74%